Same-Sex Desire in Indian Culture c y Oliver Ross. - Ross, Oliver; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
Leading to protest and debate, same-sex desire in Indian literature and film has appeared in a wide range of works since 1970 including Vikram Seth and the films of Deepa Mehta. Using these works as a focal point, among many others, Ross argues that an Euro-American notion of homosexuality is reinvented when coming into contact with Indian culture.
Keywords: Science; Science; Science, general; Electronic books